Transtheoretical Model-based Interventions are Effective in Promoting Healthy Behaviors Related to Modifiable Risk Factors of Noncommunicable Diseases: A Systematic Review - Salwa B. El-Sobkey; Bassem M. Fouda; Radwa S. Ahmed; Dalia G. El-Sayed (Dubai Medical Journal)
Introduction: Noncommunicable diseases (NCDs) such as heart diseases, type II diabetes mellitus, cancers, and stroke represent significant public health challenges globally. Modifiable risk factors, including insufficient physical activity (PA), overweight or obesity, and smoking, contribute significantly to the prevalence of these diseases. The transtheoretical model (TTM) offers a structured approach to behavior change, identifying stages of readiness and change processes. This systematic review (SR) aims to evaluate the effectiveness of TTM-based interventions in promoting healthy behaviors to mitigate these risk factors.